2013
DOI: 10.1186/1471-2334-13-572
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of coagulase-negative Staphylococcus carriage in neonates admitted to an intensive care unit in Brazil

Abstract: BackgroundNasal colonization with coagulase-negative Staphylococcus (CoNS) has been described as a risk factor for subsequent systemic infection. In this study, we evaluated the genetic profile of CoNS isolates colonizing the nares of children admitted to a neonatal intensive care unit (NICU).MethodsWe assessed CoNS carriage at admittance and discharge among newborns admitted to a NICU from July 2007 through May 2008 in one of the major municipalities of Brazil. Isolates were screened on mannitol salt agar and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 44 publications
6
22
1
Order By: Relevance
“…7 This gene has been found in more than 80% of CoNS late-onset sepsis isolates. 8 The mechanisms of dissemination of CoNS have been elucidated by many investigators 3,23 suggesting the involvement of multiple factors, social and biological, in spreading of this bacteria. It is, therefore, critical to determine the level of methicillin-resistant staphylococcus (MRS) isolates at the local and international levels 25 and to determine their clonal diversity with the use of pulsed-field gel electrophoresis (PFGE) as a gold standard genotyping technique.…”
Section: Introductionmentioning
confidence: 99%
“…7 This gene has been found in more than 80% of CoNS late-onset sepsis isolates. 8 The mechanisms of dissemination of CoNS have been elucidated by many investigators 3,23 suggesting the involvement of multiple factors, social and biological, in spreading of this bacteria. It is, therefore, critical to determine the level of methicillin-resistant staphylococcus (MRS) isolates at the local and international levels 25 and to determine their clonal diversity with the use of pulsed-field gel electrophoresis (PFGE) as a gold standard genotyping technique.…”
Section: Introductionmentioning
confidence: 99%
“…At the neonatal intensive care unit in Ö rebro University Hospital in Sweden in 2008, a case of SCCmec type V cassette transfer from MRSH to meticillin-susceptible S. aureus was reported (Berglund & Söderquist, 2008). The study conducted by Ternes et al (2013) indicated that the prevalence of SCCmec amongst CNS is high and that hospitalization increases the prevalence significantly. Whilst 60% of CNS strains isolated from patients' physiological microbiome at the moment of admission to the hospital possessed the mecA gene, the percentage of mecA-positive CNS strains at the moment of discharge from the hospital increased to 83.6%.…”
Section: Meticillin-resistant S Haemolyticus (Mrsh)mentioning
confidence: 99%
“…Multiresistant S. haemolyticus strains spread in the hospital environment (Cavanagh et al, 2014;Rodríguez-Aranda et al, 2009). Ternes et al (2013) showed that 55.9% of infants carried multiresistant CNS in their nasal cavity. Amongst them the most frequently isolated species were S. haemolyticus (38.3%) and S. epidermidis (38.0%).…”
Section: Multiresistancementioning
confidence: 99%
“…A recent study showed that the risk of acquiring nasal colonization with coagulase-negative Staphylococcus (CoNS) for all neonates admitted in a NICU was 55.9%. 18 High-risk term and preterm infants are at an increased risk of infection due to their illness, and in preterm infants due to immature skin and immune systems. 19,20 Caregiving equipment not only comes in contact with infants, but items like electrocardiogram (EKG) leads, monitoring probes, adhesive dressings, and chemical burns that can damage the epithelium can also lead to increased risk of microbial invasion.…”
mentioning
confidence: 99%